PENINGKATAN KUALITAS PENDIDIKAN ( PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM ) - Mubin, Abd. Halim (Hunafa: Jurnal Studia Islamika, 2006)
The enhancement of education quality is a complicated effort related to various things such as the formulation of a basic concept of  education that can be implemented into the  concept of Islamic education management, oriented to the prophet’s education. The purpose is to result in Islamic young generations   who are fear to God,  independent and compatative. For this puprpose, we need an effective school management, technical competence of education manager, enhancement of basic skills of teachers, leadership and supervision as a management service and accountability in education.Kata Kunci:  Kualitas pendidikan, manajemen pendidikan Islam, kepemimpinan, supervisi